The Level of the Disaster Risk Reduction and Management (DRRM) Preparedness of Elementary Schools in Southeast Butuan District - Luminarias, Genryl H.; Liquido, Ma. Gloria E. (RIRAI Publisher, 2025)
This study assessed the Disaster Risk Reduction and Management (DRRM) preparedness of elementary schools in Southeast Butuan District, focusing on practices, manifestations, and challenges faced by DRRM coordinators. Anchored on Emergency Management Theory, employing a descriptive-correlational research design, the study reveals a commendable commitment to preparedness efforts, reflecting a proactive stance towards disaster management and fostering resilience within the school community. The challenges confronting the coordinators, like insufficient training and education on DRRM concepts, limited awareness and understanding of DRRM principles, constrained budget and resources for preparedness activities, difficulties in procuring and maintaining necessary equipment and supplies, and obstacles in conducting regular drills and simulations, highlight the areas for improvement. Correlation analysis shows a significant relationship between DRRM practices and preparedness levels, emphasizing proactive engagement. The